Process Performance Analysis to Minimize Production Cost of Start-Up Culinary Business - Prabowo, Hadiyan; Farmaciawaty, Desy Anisya (Journal of Innovation, Business and Entrepreneurship, 2016)
Abstract. DeliBowl is a company engaged in the culinary field that offers a variety of rice bowl, which have been operated for a year. From the problems stated, the most significant issue is the inefficient of the production processes and the cost which causes the low of the profit margin. This problem negatively affect the performance of the company, mainly to get the high performance of the business. Therefore, the researcher conduct the research to develop the solution to the operational problems faced by DeliBowl. This research requires a benchmark to a culinary business named Yagami Ramen House which may have better operation management to be the milestone of the better recommendation which will be the result of this study. The objective of this research is to implement the proper operational strategy to push down the costs and get the high performance in order to solve their operational problems. The recommendation which is expected is after applying the strategies which will be discussed, DeliBowl process will be more efficient, low cost, and get the high performance. To do this research, the researcher collect primary data by observing the production at DeliBowl and interviewing Yagami Ramen House management. From those data, the researcher will analyze operational process, process performance and the production cost. The result of this research is the recommendation of operation management strategy which will be more efficient, low cost, and high performance. Keywords—Operational Process, Process Performance, Production Cost.